Cost and outcome of behavioural activation versus cognitive behavioural therapy for depression (COBRA): a qualitative process evaluation. Issue 4 (13th April 2017) - Finning, Katie; Richards, David A; Moore, Lucy; Ekers, David; McMillan, Dean; Farrand, Paul A; O'Mahen, Heather A; Watkins, Edward R; Wright, Kim A; Fletcher, Emily; Rhodes, Shelley; Woodhouse, Rebecca; et al.
Abstract : Objective: To explore participant views on acceptability, mechanisms of change and impact of behavioural activation (BA) delivered by junior mental health workers (MHWs) versus cognitive behavioural therapy (CBT) delivered by professional psychotherapists. Design: Semistructured qualitative interviews analysed using a framework approach. Participants: 36 participants with major depressive disorder purposively sampled from a randomised controlled trial of BA versus CBT (the COBRA trial). Setting: Primary care psychological therapies services in Devon, Durham and Leeds, UK. Results: Elements of therapy considered to be beneficial included its length and regularity, the opportunity to learn and not dwelling on the past. Homework was an important, although challenging aspect of treatment. Therapists were perceived as experts who played an important role in treatment. For some participants the most important element of therapy was having someone to talk to, but for others the specific factors associated with BA and CBT were crucial, with behavioural change considered important for participants in both treatments, and cognitive change unsurprisingly discussed more by those receiving CBT. Both therapies were considered to have a positive impact on symptoms of depression and other areas of life including feelings about themselves, self-care, work and relationships. Barriers to therapy included work, family life and emotional challenges. A subset (n=2) of BA participants commented that therapy felt too simple, and MHWs could be perceived as inexperienced. Many participants saw therapy as a learning experience, providing them with tools to take away, with work on relapse prevention essential. Conclusions: Despite barriers for some participants, BA and CBT were perceived to have many benefits, to have brought about cognitive and behavioural change and to produce improvements in many domains of participants' lives. To optimise the delivery of BA, inexperienced junior MHWs should be supported through good quality training and ongoing supervision. Trial registration number: ISRCTN27473954, 09/12/2011